American Microsystems (Phils.), Inc. Human Resource Functions - Maurin, Bo.; Mauricio, Hilario; Libunao, Eriberto Jr.; Agutaya, Ronnel (Diliman, Quezon City College of Engineering, 1993)
The original purpose of this text is to partially fulfill the requirement in I.E. 155: Industrial Systems. Yet, as the group progressed, a common interest developed among its members toward the assigned topic namely The Human Resource Function of American Microsystems, Inc. (Phils.). As a result, what was originally a mere curious attitude is now the driving force that propelled the group to endure the jam-packed length of EDSA enroute to Sucat and proceed with the Documentation, Analysis and Design of the said function. This resulted to nearly three (3) kilograms of hardbound paper which you are now pre-occupied with. As indicated before, there will be three parts to this voluminous project study: Documentation, Systems Analysis and Systems Design. In addition, a brief background of the study as well as that of the (again) assigned site, is provided in the Introduction. DOCUMENTATION: Documenting the present system was painstakingly achieved through personal interviews with every individual who has a direct relation with the Human resource Function. Yet, focus was deviated to the five (5) personnel in the Human Resources Department. This resulted into a detailed, step by step process description of all the existing subfunctions. In the corresponding section of the study, these step by step process descriptions is presented through a process flow chart of the basic compound procedures involved complemented by an in-depth description of each procedure which highlights the following aspects: 1) The procedure/step description; 2) The individual(s) involved; 3) The output(s) of the procedure; and 4) The form(s) used. In addition, each subfunction is supplemented by the process: Definition, Objective, Policy(ies), Scope, and Applicable Documents. As can be seen later on, additional information is supplied which is designed to enhance the reader's comprehension of the processes. Pre-empting the entire analyses of the system, the members of the group would like to stress both its individual and collective difficulties in accomplishing the said task. This is primarily due to the absence of a formal, structured step by step process. Instead, most, if not all, of the existing subfunctions are conducted in a very subjective manner which is characteristic of service-oriented processes. SYSTEM ANALYSIS: In analyzing the existing methods employed, the focus is again shifted to only three (3) main areas namely: 1) Recruitment, 2) Training, and 3) Work Schedule Control. It will be important to note that the Recruitment process being referred to is the compound process of Recruitment, Selection, and Orientation. In addition, in contrast to the extensiveness of the Documentation stage, the Systems Analysis is limited to the said subfunctions not by the group, but instead for the group by the proponents of the Human Resource Function. In this part of the study, areas within the said subfunctions that poses an opportunity for improvement were identified and probable solutions explored. Yet, aside from the aforementioned characteristic of the Human Resource Function (which is being informal and unstructured), another characteristic hindered the group from its proceedings: There were no pertinent statistical data!! SYSTEMS DESIGN: The Systems Design portion of this study is an attempt to inch closer to the much desired Ideal System. However, it should be noteworthy to know that such a system does not, cannot, and will not exist. Instead, it serves only as a mere model by which one can gauge the amount of improvements that still need to be installed. In all three subfunctions (stated above), recommended solutions were developed based on the preceding analyses. These alternative courses of actions are then evaluated, comparing their derived benefits with the corresponding disbenefits. Once proven to be desirable each proposal is then juxtaposed with the current practice to determine if they are indeed equally or even more desirable. As a result, the group arrived at what its members deem as "close to the ideal" (at least for the time being) as possible.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 155 : Industrial Systems Design
Keywords: American Microsystems (Phils.), Inc; Personnel management; International business enterprises--Personnel management; System design